The southern river otter (Lontra provocax): insights from the perspective of Andean Patagonian ethnozoology - Pozzi, Carla; Ladio, Ana H. (Ethnobiology and Conservation, 2021)
Animals play a significant role in many cultures around the world. The southern river otter Lontra provocax (known locally as the “huillín”) is endemic to southern Argentina and Chile, and is currently in danger of extinction. Mapuche communities have always lived closely alongside their animal resources, generating unique bonds with them. The objective of this work is to obtain an overview of the importance given to this species in the literature of the region with regard to the nature-culture connection. A systematic bibliographical review was carried out using reference libraries and web browsers. From all the sources analysed, 110 were selected which held biocultural information. The main approach used was ecological; however, the ethnohistorical texts provided the richest information on the bond between this otter and humans. The Mapuche name “huillín” appears in all the publications analysed, showing its continuity over time. Of all the zootoponyms found, 87.5% were Chilean and 12.5% were Argentine. The Argentine case is found in Nahuel Huapi lake, and is worthy of note as its name could involve the huillín. The results of this work increase our knowledge of the biocultural heritage of our region, and enable us to reflect on the associated historical and political processes.